2019
DOI: 10.1155/2019/9637479
|View full text |Cite
|
Sign up to set email alerts
|

Xiao-Qing-Long Tang Prevents Cardiomyocyte Hypertrophy, Fibrosis, and the Development of Heart Failure with Preserved Ejection Faction in Rats by Modulating the Composition of the Gut Microbiota

Abstract: Background. Changes in the gut microbiota are associated with cardiovascular disease progression. Xiao-Qing-Long Tang (XQLT), a traditional herbal formula, has an anti-inflammatory effect and regulates the steady state of the immune system, which is also associated with the progression of heart failure with preserved ejection faction (HFpEF). In this study, we investigated whether XQLT could contribute to prevent the development of HFpEF and whether the modulation of the gut microbiota by this herbal formula c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 36 publications
1
20
0
Order By: Relevance
“…These results were in line with earlier reports that showed that the improvement of cardiac in ammation and brosis was associated with decrease in blood pressure. [10,38] Based on the results of the network analysis and molecular docking, several targets such as AKT1, VEGFA, eNOS, ICAM-1, PTGS2, and ALB could be associated with the potential effect of GZD on hypertension. For example, AKT1 directly participates in the phosphorylation of eNOS at serine 1177, which could increase enzyme activity, NO production, and angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…These results were in line with earlier reports that showed that the improvement of cardiac in ammation and brosis was associated with decrease in blood pressure. [10,38] Based on the results of the network analysis and molecular docking, several targets such as AKT1, VEGFA, eNOS, ICAM-1, PTGS2, and ALB could be associated with the potential effect of GZD on hypertension. For example, AKT1 directly participates in the phosphorylation of eNOS at serine 1177, which could increase enzyme activity, NO production, and angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…To further confirm the effects of GZD on cardiac fibrosis, immunohistochemical staining was performed to evaluate the expression levels of collagens I and III in the left ventricle. Collagens I and III are two important molecular mediators of collagen deposition and extracellular matrix (ECM) alterations during the pathological fibrotic process [ 24 ]. Furthermore, Collagens I and III also play a relatively important role in the PPI network.…”
Section: Methodsmentioning
confidence: 99%
“…Evidence-Based Complementary and Alternative Medicine cardiomyocyte hypertrophy and fibrosis, and it could improve the intestinal mucosal histology by regulating the composition of gut microbiota [51]. Tong-Xie-Yao-Fang can effectively improve the intestinal permeability and enhance the intestinal mucosal barrier function [52].…”
Section: Gut Microbiota and Herbalmentioning
confidence: 99%